Numerical Study for Optimal Design of Geosynthetic Reinforced Soil (GRS) Walls - DASTGERDI, Rashid Hajivand; BAHRAMI, Nima; KAZEMI, Kamran; WAQAR, Muhammad Faisal; MALINOWSKA, Agnieszka (Engineering Transactions, 2024)
The geosynthetic reinforced soil (GRS) system finds applications in numerous geotechnical projects, including retaining walls, road and railway embankments, slope stability structures, landfill structures, etc. This is attributed to its ability to enhance soil bearing capacity while minimizing deformations. Over the recent decades, extensive research has been conducted to comprehensively understand the behavior of GRS systems. In our research, we initially validate two laboratory tests using finite element (FE) modeling and conduct a parametric study. Our findings demonstrate that increasing the stiffness of layers from the bottom to the top of the wall significantly reduces wall displacements, approaching a state where all layers have uniform stiffness.Additionally, we investigate the plastic zone and the length of geogrids in each layer. Our results indicate that reducing the length of layers from top to bottom, similar to the plastic zone shape, does not impact displacements and forces within the layers. Simultaneously increasing stiffness with height and decreasing geogrid layer lengths within the plastic zone reduces the cost of GRS wall construction.